Initial Low Levels of Suicidal Ideation Still Improve After Cognitive Behavioral Therapy for Insomnia in Regular Psychiatric Care - Jernelöv, Susanna; Forsell, Erik; Kaldo, Viktor; Blom, Kerstin (Frontiers in Psychiatry, 2021)
Insomnia disorder is highly prevalent, and has been identified as a risk factor for many psychiatric problems, including depression, suicide ideation and suicide death. Previous studies have found that cognitive behavioral therapy for insomnia (CBT-I) reduced depression and suicidal ideation in samples with high levels of suicidal ideation. This study aims to investigate associations of CBT-I with suicidal ideation in a sample of 522 patients primarily seeking treatment for insomnia in regular psychiatric care. The sample had high pretreatment insomnia severity levels and a relatively high level of comorbid depression symptoms. Suicidal ideation levels were relatively low pretreatment but still improved significantly after CBT-I. Contrary to previous findings, the strongest predictor of changes in suicidal ideation were improvements in depressive symptoms, rather than improvements in insomnia. We conclude that suicidal ideation may not be a major problem in these patients primarily seeking treatment for insomnia, despite comorbid depressive symptoms, but that suicidal ideation still improves following CBT-i. Considering the increased risk for patients with untreated insomnia to develop depression, this finding is of interest for prevention of suicidal ideation.